Diabetes and work: 12-year national follow-up study of the association of diabetes incidence with socioeconomic group, age, gender and country of origin. Issue 8 (December 2014) - Poulsen, Kjeld; Cleal, Bryan; Willaing, Ingrid
Aims: To investigate the extent and socioeconomic distribution of incident diabetes among the Danish working-age population. Methods: The Danish National Diabetes Register was linked with socioeconomic and population-based registers covering the entire population. We analysed the 12-year diabetes incidence using multivariate Poisson regression for 2, 086, 682 people, adjusting for gender, 10-year age groups, main population groups defined by country of origin, and seven socioeconomic groups: professionals, managers, technicians, workers skilled at basic level, unskilled workers, unemployed and pensioners. Results: The crude 12-year incidence of diabetes was 5.8%. The saturated multivariate model, adjusted for gender, age, country of origin and socioeconomic status; showed a relative risk (RR) for diabetes incidence of 1.44 for male (reference: female), 3.95 for the age range of 50–59 years (reference: 30–39 years), 2.07 for unskilled workers (reference: professionals) and 2.15 for people from countries of 'non-Western origin' (reference: Danish origin). Conclusions: Diabetes incidence increases with age, male gender and low socioeconomic status; and also among people from countries of 'non-Western origin'. The results indicate that getting a more senior workforce will substantially increase the proportion of workers with diabetes, especially among already vulnerable groups.